Pengaruh Ecomomic Value Added, Market Value Added, Dan Tobin’s Q Terhadap Harga Saham (Studi Empiris Pada Industri Perbankan yang terdaftar LQ-45 Periode Februari-Juli 2021) - Aswin Nur Syahbana; Budi Wahono; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine whether Economic Value Added, Market Value Added and Tobin's Q partially and simultaneously affect stock prices. This research was conducted in the banking industry registered with LQ-45 for the period February-July 2021 with a total of 6 companies and 6 samples of financial statements. The type of research used is quantitative research. The data analysis method in this study used statistical analysis with the SPSS program. The results showed that the Economic Value Added (EVA) had a significant and positive effect on the LQ-45 Stock Price, the Market Value Added (MVA) had no significant effect on the LQ-45 stock price, Tobins'Q had no significant effect on the LQ-45 Stock Price. The contribution in this study can be an evaluation for potential investors who want to invest in banking sector stocks to be able to understand, find out what factors affect stock prices in banking. Keyword: Economic Value Added (EVA), Market Value Added (MVA), Tobins'Q and LQ-45 stock price